2016
DOI: 10.1017/s0007485316000109
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of the pygidial gland secretion of the troglophilic ground beetleLaemostenus(Pristonychus)punctatus(Dejean, 1828) (Insecta: Coleoptera: Carabidae)

Abstract: The antimicrobial activity of the pygidial gland secretion released by adult individuals of the troglophilic ground beetle Laemostenus (Pristonychus) punctatus (Dejean, 1828), applying microdilution method with the aim to detect minimal inhibitory concentration, minimal bactericidal concentration and minimal fungicidal concentration, has been investigated. In addition, morphology of the pygidial glands is observed. We have tested 16 laboratory and clinical strains of human pathogens - eight bacterial both gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…In previous studies, it was assumed that the antimicrobial activity of the secretion of L. (P.) punctatus is probably caused by the interaction of several chemical components acting synergistically (Nenadić et al, 2016b;Nenadić, 2019), but in this study we found that the selected fatty acids from the secretion were indifferent in combination as formic acid achieved much stronger antimicrobial activity compared to oleic acid. 10.3389/fevo.2023.1148309 In this study, the beta-lactam antibiotics ampicillin and cephalexin and the aminoglycoside streptomycin were found to have weaker antibacterial activity than the tested secretion and formic acid.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…In previous studies, it was assumed that the antimicrobial activity of the secretion of L. (P.) punctatus is probably caused by the interaction of several chemical components acting synergistically (Nenadić et al, 2016b;Nenadić, 2019), but in this study we found that the selected fatty acids from the secretion were indifferent in combination as formic acid achieved much stronger antimicrobial activity compared to oleic acid. 10.3389/fevo.2023.1148309 In this study, the beta-lactam antibiotics ampicillin and cephalexin and the aminoglycoside streptomycin were found to have weaker antibacterial activity than the tested secretion and formic acid.…”
Section: Discussioncontrasting
confidence: 52%
“…10.3389/fevo.2023.1148309 In this study, the beta-lactam antibiotics ampicillin and cephalexin and the aminoglycoside streptomycin were found to have weaker antibacterial activity than the tested secretion and formic acid. In contrast, Nenadić et al (2016b) noted that the commercial antibiotics streptomycin and ampicillin and the antifungal agents ketoconazole and bifonazole generally exhibited higher antimicrobial potential against all tested bacterial and fungal strains, with the exception of Penicillium ochrochloron, which was found to be more resistant to ketoconazole and more sensitive to the pygidial gland secretion of L. (P.) punctatus (MIC 1.1 mg/mL, MBC 2.2 mg/mL). Interestingly, the secretion displayed a higher antibacterial potential against the non-resistant E. coli, P. aeruginosa, and S. aureus strains in the current study, with MIC values about 100 times lower.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations